FRIEND TO ORGANIZE AN ARGUMENTATIVE TEXT - Faisal Faisal (University of Muhammadiyah Purwokerto, 2013)
Writing is a process that helps the students develop their ideas and logical thinking. Principally, to write means to try to produce a written message. Because of these facts, it is necessary for teachers and students to master it well as writing plays a very important role in many processes including teaching and learning proc-esses. However, in the real teaching and learning process, junior high students who have been accustomed to LKS (Student Worksheet) consider writing a boring activity. They have to just fill in the blanks, answer the ques-tions, and rearrange jumbled paragraphs in spite of writing their own ideas based on certain topics. This be-comes the drawbacks for them to get actively involved in writing activities. To overcome that, FRIEND standing for Fact, Reason, Point, Elaboration and Decision is considered help-ful to improve learners’ ability to develop an argumentative essay. FRIEND helps learners to write well-developed and properly organized essay since it provides systematic ways to do so. Besides, FRIEND actually gives learners an easy way to think, express, and organize their ideas into a good argumentative essay. . Keywords: FRIEND, argumentative essay